2013
DOI: 10.1021/sb3001084
|View full text |Cite
|
Sign up to set email alerts
|

Designing and Producing Modified, New-to-Nature Peptides with Antimicrobial Activity by Use of a Combination of Various Lantibiotic Modification Enzymes

Abstract: Lanthipeptides are peptides that contain several post-translationally modified amino acid residues and commonly show considerable antimicrobial activity. After translation, the amino acid residues of these peptides are modified by a distinct set of modification enzymes. This process results in peptides containing one or more lanthionine rings and dehydrated Ser and Thr residues. Previously, an in vivo lanthipeptide production system based on the modification machinery of the model lantibiotic nisin was reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
99
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(103 citation statements)
references
References 38 publications
4
99
0
Order By: Relevance
“…These resulting pNZ-nisA derivatives were digested by HindIII and XhoI and ligated with a fragment containing the transcriptional attenuator and ltnJ to generate 19 different derivatives of pNZ-nisA-T-ltnJ (Table 1). This fragment was amplified with the primers P-for-HindIII-T-ltnJ and P-ltnJ-rev-XhoI (Table 2) using pNZ-nisA-T-ltnJ (18). By applying two sets of round PCR on pNZ-nisA with two pairs of primers, P-for-K34L/P-rev-K34L and P-for-S29insKIH/P-rev-S29insKIH (Table 2), pNZ-nisin(⌬30 -34)-KI-HIHVSL was created (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…These resulting pNZ-nisA derivatives were digested by HindIII and XhoI and ligated with a fragment containing the transcriptional attenuator and ltnJ to generate 19 different derivatives of pNZ-nisA-T-ltnJ (Table 1). This fragment was amplified with the primers P-for-HindIII-T-ltnJ and P-ltnJ-rev-XhoI (Table 2) using pNZ-nisA-T-ltnJ (18). By applying two sets of round PCR on pNZ-nisA with two pairs of primers, P-for-K34L/P-rev-K34L and P-for-S29insKIH/P-rev-S29insKIH (Table 2), pNZ-nisin(⌬30 -34)-KI-HIHVSL was created (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Another class II lantibiotic, deoxyactagardine B (NVB302; Novacta Biosystems Limited), is undergoing a phase I clinical trial as a drug candidate for the treatment of Clostridium difficile infections (14). Furthermore, recent research has shown that some class III lanthipeptides have unexpected bioactivity to relieve neuropathic pain (15) and as antiviral compounds (16).Besides the common (methyl)lanthionine, more than 15 extra structures have been unveiled in lanthipeptides playing a significant role in antimicrobial activity, resistance against proteases, and/or physicochemical resistance (12,(17)(18)(19)(20). For instance, D-alanine was found within two lantibiotics: lactocin S and the twocomponent lantibiotic lacticin 3147 (Fig.…”
mentioning
confidence: 99%
See 3 more Smart Citations